2022
DOI: 10.1126/sciadv.abm9982
|View full text |Cite
|
Sign up to set email alerts
|

The direct drivers of recent global anthropogenic biodiversity loss

Abstract: Effective policies to halt biodiversity loss require knowing which anthropogenic drivers are the most important direct causes. Whereas previous knowledge has been limited in scope and rigor, here we statistically synthesize empirical comparisons of recent driver impacts found through a wide-ranging review. We show that land/sea use change has been the dominant direct driver of recent biodiversity loss worldwide. Direct exploitation of natural resources ranks second and pollution third; climate change and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
127
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 349 publications
(134 citation statements)
references
References 90 publications
3
127
1
3
Order By: Relevance
“…Land use-the recent main driver of biodiversity loss worldwide [1,2]-affects soil assemblages differently from those above ground. As hypothesised, croplandwhere tillage, pesticides and fertilisers disturb soil biodiversity [31,32]-reduces abundance even more in the soil than above ground.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Land use-the recent main driver of biodiversity loss worldwide [1,2]-affects soil assemblages differently from those above ground. As hypothesised, croplandwhere tillage, pesticides and fertilisers disturb soil biodiversity [31,32]-reduces abundance even more in the soil than above ground.…”
Section: Discussionmentioning
confidence: 99%
“…Author details 1 Science and Solutions for a Changing Planet DTP, and the Department of Life Sciences, Imperial College, London, UK. 2 Natural History Museum, London, UK. 3 United Nations Environment Programme World Conservation Monitoring Centre, Cambridge, UK.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, three decades of global change research has shown that biodiversity conservation can improve the magnitude and resiliency of many ecosystem functions and services, such as providing a large pool for carbon sequestration and storage for climate mitigation. Second, advances in global change biology have pinpointed the primary drivers of biodiversity loss, the most prominent being land/sea use change, overexploitation of marine and natural resources, and pollution, with climate change and invasive species contributing significantly but to a lesser degree ( 1 ). Such findings provide clear guidance for policy development.…”
mentioning
confidence: 99%